A nanobody-based molecular toolkit for ubiquitin–proteasome system explores the main role of survivin subcellular localization - Miao, Hui; Liu, Chang; Ouyang, Hao; Zhang, Peiwen; Liu, Yuping; Zhang, Chen; Deng, Changping; Fu, Yunhui; Niu, Jinping; Zheng, Wenyun; You, Fang; Yang, Yi; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Targeted protein degradation is a powerful tool for determining the function of specific proteins nowadays. Survivin is the smallest member of the inhibitor of apoptosis proteins (IAP) family. It exists in the cytoplasm and nucleus of cells. But the exact function of Survivin in different subcellular locations retained unclear update due to the lack of effective and simple technical means. In this study, we created a novel nanoantibody-based molecular toolkit, namely ubiquitin-proteasome system (Nb4A-Fc-T2A-TRIM21), that can target to degrade survivin localized in cytoplasmic and cell nuclear by ubiquitinating, and by which to verify the potential roles of survivin subcellular localization. And the results showed that the cytoplasmic Survivin mainly plays an anti-apoptotic function by directly or indirectly inhibiting the caspase pathway, and the nuclear Survivin mainly promotes cell proliferation and participates in the regulation of the cell cycle. In addition, Nb4A-Fc-T2A-TRIM21 system can degrade the endogenous Survivin protein in a large amount by the ubiquitin-proteasome pathway, and the system can provide theoretical support for ubiquitination degradation targeting other endogenous proteins.